Eco-optimizing rice-wheat system of Eastern Indo-Gangetic plains of India through resource conservation technologies: insights from field experiments and modeling - Reddy, K. Srikanth; Parihar, C. M.; Panneerselvam, P.; Sarkar, Ayan; Nayak, Hari Sankar; Patra, Kiranmoy; Sena, D. R.; Reddy, G. Sreeja; Sinha, Alok; Bharadwaj, Sneha; Kumar, Sunil; Kumar, Virender (Frontiers Media, 2025)
In eastern India, the rice-wheat cropping system (RWCS) faces challenges like poverty, fragmented landholdings, and resource overexploitation, with smallholder farmers prioritizing short-term gains through excessive water and nitrogen use. To address these issues, our study combined field experiments and the DNDC crop simulation model to evaluate the resilience, viability, and environmental sustainability of RWCS under conservation agriculture (CA) with varying irrigation methods and nitrogen rates at the International Rice Research Institute-South Asia Regional Center (ISARC), Varanasi, India. The treatments included: (1) Puddled transplanted rice followed by zero-tilled wheat with flood irrigation (PTR-ZTW-F), (2) Direct-seeded rice followed by ZTW with flood irrigation (DSR-ZTW-F), (3) DSR followed by ZTW with surface drip fertigation (DSR-ZTW-SD), and (4) DSR followed by ZTW with subsurface drip fertigation (DSR-ZTW-SSD), evaluated under 75% and 100% recommended nitrogen dose and nitrogen control plots. The DNDC model accurately predicted soil mineral N (: R2 = 0.74, RRMSE = 52.9%; : R2 = 0.79, RRMSE = 63.5%), water-filled pore space (R2 = 0.85, RRMSE = 20.9%), soil temperature (R2 = 0.91, RRMSE = 4.6%), redox potential (R2 = 0.82, RRMSE = 24.1%), system productivity (R2 = 0.93, RRMSE = 7.8%), and nitrogen uptake (R2 = 0.86, RRMSE = 18.1%). DSR-ZTW systems with drip fertigation significantly enhanced sustainability and productivity compared to PTR-ZTW system, where CH4 emissions were reduced by 70%–80% and global warming potential reduced by 56%, despite higher N2O emissions. Additionally, DSR-ZTW-SSD achieved the highest system yield (12.8 t ha−1), minimized water losses, and improved nitrogen use efficiency. Also, TOPSIS analysis ranked DSR-ZTW-SSDF as the most sustainable system, achieving the highest yield and resource use efficiency, while significantly reducing GHG emissions. The study underscores the potential of integrating CA, drip fertigation, and DSR to enhance productivity, conserve resources, and improve the sustainability of RWCS.